Regression Analysis - Wilson, J .Holton (Business Expert Press, 2012)
Ebook from IG Library ; The technique of regression analysis is used so often in business and economics today that an understanding of its use is necessary for almost everyone engaged in the field. This book will teach you the essential elements of building and understanding regression models in a business/economic context in an intuitive manner.